ENHANCING PRIMARY SCHOOL STUDENT PARTICIPATION IN EFL CLASSES THROUGH GAME-BASED LEARNING DURING AFTERNOON SESSIONS - Avilia; A. Gusti Efendy (e-Journal of ELTS (English Language Teaching Society), 2025)
This study investigates the impact of Game-Based Learning (GBL) on student participation during afternoon English as a Foreign Language (EFL) lessons in a Grade III primary school classroom. Declining learner engagement during afternoon sessions represents a persistent challenge in primary EFL instruction, as accumulated fatigue and diminished concentration frequently impede students’ active involvement in teacher-led question-and-answer activities. This Classroom Action Research (CAR) was conducted at SD Katolik Santo Yohanes Kalipare, Malang Regency, East Java, involving eight Grade III students as research participants. Data were collected through systematic quantitative observation, recording both the number of actively participating students and the frequency of individual responses during question-and-answer sessions, before and after the intervention. The GBL intervention consisted of individual interactive quizzes implemented as an ice-breaking activity for 10–15 minutes at the midpoint of the lesson, incorporating a points-based reward system. Findings revealed a significant increase in student participation. Prior to the intervention, only 3 of 8 students (37.5%) actively participated, with a mean response frequency of 0.375 answers per student. After the GBL intervention, the number of active students rose to 8 of 8 (100%), with the mean response frequency increasing to 2.125 answers per student. These results indicate that individual interactive quizzes as a GBL strategy effectively re-energise students and encourage active participation during afternoon EFL lessons. The study recommends the systematic integration of GBL strategies in primary EFL instruction, particularly during high-fatigue lesson periods.